Landscape Design Strategies for Healthy Aging-in-Place in Communities: Case Studies from Suzhou, China - Da Huo; Fei Chen; Bing Chen (Buildings, 2024)
As the global population ages, the World Health Organization promotes “Healthy Aging” to enhance the quality of life for the elderly. In China, with its substantial aging population, the “9073” elderly care mode, which prioritizes community-based care, was implemented in 2011. However, the specific needs of elderly residents in different climatic and cultural contexts are often overlooked. This study addresses this gap by examining how community green space design can support healthy aging, using Suzhou as a case study due to its significant elderly population. This research examines the relationship between community environments, elderly needs, and behaviors. Our findings reveal that elderly residents have complex needs, seeking safety, comfort, health, social interaction, and spiritual richness simultaneously. A mismatch was observed between their stated preferences for features like seating and shade and their actual usage patterns, suggesting that existing green spaces may not fully meet their needs. This study underscores the importance of incorporating both expressed preferences and proactive design strategies to enhance the healthy benefit of community green spaces. These insights support the “Healthy China 2030” strategy and promote the well-being of elders, contributing to sustainable urban regeneration.